Transition to home after very preterm birth: improving outcomes of children and their families—a systematic review protocol - Beatrice Latal; Ulrike Held; Ursula Kiechl-Kohlendorfer; Sandra Siegfried; Vivienne Engel; Valentina Mauron-Papadimitriou; Lea Bührer; Laura Ebner; Lena Keller; Martina Gosteli (BMJ Open)
Introduction Medical progress has significantly improved the survival rates of very preterm-born infants in recent decades. Nevertheless, these infants are still at increased risk for long-term impairments as compared with term-born infants. While the homecoming of a preterm-born infant is long-awaited and brings relief to families, it also marks the end of intensive monitoring and highly specialised professional care. This situation often leaves parents coping with anxiety and a sense of unpreparedness, as they navigate the transition to home. Correspondingly, the WHO advocates for additional support for parents of preterm infants following the transition to home. According to the WHO, preparation for this transition yields positive effects on crucial aspects such as nutrition, parent–child interaction and parental well-being. However, there is significant heterogeneity as to which interventions are in place and regarding their level of efficacy. Consequently, we aimed to provide an overview of existing transition-to-home interventions and their efficacy by conducting a systematic review of the literature.Methods and analysis We will perform a systematic review of interventions aiming at improving the transition to home process for very preterm-born infants and their parents and will search the following databases: Cochrane, Medline, CINAHL, EMBASE and PsycINFO. Our main aim is to provide an overview of existing transition-to-home interventions and their efficacy in categories of intervention types. We will not predefine specific outcomes, but we will describe, assess and summarise the outcomes of the included studies. All reported outcomes will be recalculated to the scale of standardised mean differences. Meta-analysis will be performed with a random-effects model to account for expected large between-study heterogeneity.Ethics and dissemination No ethics approval was necessary for this study. The aim of our systematic review is to provide a comprehensive overview of current interventions designed to improve the transition from hospital to home. Subsequently, it will show the individual effect of these interventions and pool effect sizes if possible. The most promising interventions will then be combined and used as the basis of a subsequent randomised controlled trial of a new transition-to-home intervention. The results of the study will be published in a peer-reviewed journal.PROSPERO registration number The systematic review protocol was registered with the International Prospective Register of Systematic Reviews (PROSPERO) on 30 August 2023. PROSPERO CRD42023455401.